Tranformasi Kurikulum Sebagai Upaya Penguatan Kemampuan Siswa Di Tengah Perkembangan Teknologi - Septi Wulandari, Rohadatul Aisy, Riska Maulita, Sofia Dzatil izah, Abdurrahmansyah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The rapid development of technology in the digital era has brought significant changes to the field of education, including the learning process and curriculum implementation. This condition requires schools and educators to adapt learning systems so that students are able to develop competencies relevant to the demands of the times. Curriculum transformation becomes an important effort to strengthen students’ abilities, especially in critical thinking, creativity, collaboration, and digital literacy. This article aims to analyze the role of curriculum transformation in strengthening students’ abilities amidst rapid technological developments. The method used in this study is a qualitative approach through literature review by examining various relevant books and scientific articles related to curriculum transformation and educational technology. The results of the study indicate that curriculum transformation can be carried out through the integration of technology in learning, the use of innovative teaching strategies, and the development of competency-based assessments. In addition, teachers play a crucial role in designing adaptive and interactive learning environments that support students’ active participation. Therefore, curriculum transformation is expected to be able to improve the quality of education and prepare students to face the challenges of the digital era with strong knowledge, skills, and character